Comparing protein adsorption onto alumina and silica nanomaterial surfaces: clues for vaccine adjuvant development - Park, Hyeonjin (2022)
Protein adsorption onto nanomaterial surfaces is important for various nanobiotechnology applications such as biosensors and drug delivery. Within this scope, there is growing interest to develop alumina- and silica-based nanomaterial vaccine adjuvants and an outstanding need to compare protein adsorption onto alumina- and silica-based nanomaterial surfaces. Herein, using alumina- and silica-coated arrays of silver nanodisks with plasmonic properties, we conducted localized surface plasmon resonance (LSPR) experiments to evaluate real-time adsorption of bovine serum albumin (BSA) protein onto alumina and silica surfaces. BSA monomers and oligomers were prepared in different water-ethanol mixtures and both adsorbing species consistently showed quicker adsorption kinetics and more extensive adsorption-related spreading on alumina surfaces as compared to on silica surfaces. We rationalized these experimental observations in terms of the electrostatic forces governing protein-surface interactions on the two nanomaterial surfaces and the results support that more rigidly attached BSA protein-based coatings can be formed on alumina-based nanomaterial surfaces. Collectively, the findings in this study provide fundamental insight into protein-surface interactions at nanomaterial interfaces and can help to guide the development of protein-based coatings for medical and biotechnology applications such as vaccines.